Industry Applications Society 40th Annual Petroleum and Chemical Industry Conference
DOI: 10.1109/pcicon.1993.337409
|View full text |Cite
|
Sign up to set email alerts
|

Saving energy and protecting the environment through a retrofit lighting program

Abstract: Lighting typically represents 40 percent of the total electrical energy consumption in commercial buildings and 9 percent of the energy consumption in industrial plants. New technological advances in the manufacture of fluorescent lamps and ballasts have made it possible to save more than 35 percent of current lighting energy. The total possible savings in the US. are estimated to be $18 billion per year [l]. These figures indicate tremendous potential both for monetary savings and reduction of pollutants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has been reported that lighting accounts for about 15 -20% of the average home's electricity consumption, whereas it represents about 40% of total electrical energy consumption in commercial buildings and about 9% of the energy consumption in industrial plants [1][2][3].…”
Section: Nomenclature and Abbreviationsmentioning
confidence: 99%
“…It has been reported that lighting accounts for about 15 -20% of the average home's electricity consumption, whereas it represents about 40% of total electrical energy consumption in commercial buildings and about 9% of the energy consumption in industrial plants [1][2][3].…”
Section: Nomenclature and Abbreviationsmentioning
confidence: 99%
“…Records show that lighting dominates energy consumption. For instance, it consumes 40% of the total electrical energy in commercial buildings and about 9% in industrial plants [1]. In particular, fluorescent lighting (FL) consumes about 20% of total lighting consumption [2].…”
Section: Introductionmentioning
confidence: 99%